Discourse Network Analysis Of Tabungan Perumahan Rakyat (TAPERA) In Online Media Coverage - Pribadi, Firman; Gema Nusantara Bakry; Catur Nugroho (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aims to investigate the discourse network surrounding the Tabungan Perumahan Rakyat (Tapera) program in online media coverage. Using the Discourse Network Analysis (DNA) method, the research examines the relationships among entities, concepts, and arguments presented in news coverage published between May 27, 2024, and June 10, 2024. A total of 16 articles from nine online media platforms were analyzed, resulting in the identification of 22 concepts and 33 actors actively involved in the discussion. The findings reveal two major groups: supporters and opponents of the Tapera program. Government actors predominantly support the initiative, while political parties and non-governmental organizations express resistance. The study highlights key issues such as program benefits, concerns about forced participation, and transparency. By mapping the discursive dynamics, this research provides valuable insights into how media shapes public opinion and perception of housing policy. The findings underscore the need for enhanced public communication and in-depth policy evaluation to ensure successful implementation. Keywords: Discourse Network Analysis, online media, Tapera, housing policy, media analysis